Research Update: Citrus Undercover Production Systems and Whole Tree Thermotherapy - Schumann, Arnold; Waldo, Laura; Wright, Alan (EDIS, 2016)
Research for producing huanglongbing (HLB)-free fresh Florida citrus with covered production systems began at the University of Florida/Institute of Food and Agricultural Sciences (UF/IFAS) Indian River Research and Education Center in 2013 and at the Citrus Research and Education Center (CREC) in 2014. These citrus undercover production systems (CUPS) evolved from the already proven psyllid-proof, screen-covered citrus nurseries that were introduced in Florida more than a decade ago to allow the propagation of disease-free transplants for the citrus industry. The protected citrus experiments in both locations are approximately 1 acre each and consist of 14-foot-high pole and cable frame architecture, covered with 50-mesh, anti-insect screen.